The Innovation Platform Designing of Online Learning for Study on the Field in the Medical Rural Studies Module During the COVID-19 Pandemic - Churproong, Seekaow; Chanvirat, Kanala; Saewong, Parichad; Vaenthaisong, Prachasan (Ratchaphruek Journal, 2021)
As a result of coronavirus infectious disease 2019 (COVID-19), a study on the field in real situations of Medical Rural Studies (MRS) 1-4 modules at Suranaree University of Technology (SUT) for medical and dental students was changed to a study online. This article purposed the designing of online learning in the MRS3 module which was provided 9 tasks that related to the COVID-19 situation. For example, COVID-warrior in a white gown, being a rural doctor, home visit care for the quality of life assessment, workers’ story, learning of wound care, critical thinking about the public health care system, self-reflection, online transformative theatre via the video conference program. All tasks were designed by following the major objectives of the module. Self-awareness, patients’ and others’ perception, and systems thinking were the main concept of the MRS module. The innovation platform designing of online learning for study on the field in the MRS module during the COVID-19 pandemic so challenged to the course director. However, the major key success factor was the facilitators that helped students in both individual and group learning styles achieved the objectives of the MRS module.Time management and content completion were the advantage for self-directed learning followed as tasks assigned. In the future, the innovation platform designing of online learning for a study on the field might be the benefit to develop the medical curriculum.